Anticancer Properties of Graviola (Annona muricata): A Comprehensive Mechanistic Review. (30th July 2018) - Rady, Islam; Bloch, Melissa B.; Chamcheu, Roxane-Cherille N.; Banang Mbeumi, Sergette; Anwar, Md Rafi; Mohamed, Hadir; Babatunde, Abiola S.; Kuiate, Jules-Roger; Noubissi, Felicite K.; El Sayed, Khalid A.; Whitfield, G. Kerr; Chamcheu, Jean Christopher
Abstract : Graviola ( Annona muricata ) is a small deciduous tropical evergreen fruit tree, belonging to the Annonaceae family, and is widely grown and distributed in tropical and subtropical regions around the world. The aerial parts of graviola have several functions: the fruits have been widely used as food confectionaries, while several preparations, especially decoctions of the bark, fruits, leaves, pericarp, seeds, and roots, have been extensively used in traditional medicine to treat multiple ailments including cancers by local communities in tropical Africa and South America. The reported therapeutic benefits of graviola against various human tumors and disease agents in in vitro culture and preclinical animal model systems are typically tested for their ability to specifically target the disease, while exerting little or no effect on normal cell viability. Over 212 phytochemical ingredients have been reported in graviola extracts prepared from different plant parts. The specific bioactive constituents responsible for the major anticancer, antioxidant, anti-inflammatory, antimicrobial, and other health benefits of graviola include different classes of annonaceous acetogenins (metabolites and products of the polyketide pathway), alkaloids, flavonoids, sterols, and others. This review summarize s the current understanding of the anticancer effects of A. muricata and its constituents on diverse cancer types and disease states, as well as efficacy and safety concerns. It also includes discussion of our current understanding of possible mechanisms of action, with the hope of further stimulating the development of improved and affordable therapies for a variety of ailments.